Crescimento e desenvolvimento de chloris distichophylla lag. em diferentes condições de ambiente - Gaviraghi, Fernando (2012)
This study aimed to: evaluate and characterize the development of Chloris distichophylla Lag species, and identify the effect of soil conditions and shade in its development, The experiments were conducted in the city of Passo Fundo - RS, Brazil, during the agricultural year of 2010-2011. Experiments were performed to evaluate the development of the plant in shading conditions, soil pH and soil compaction. Plants were originated from seeds collected from plants that exist in adjacent areas of crops and roadsides of that region. Chloris distichophylla Lag is a cockle with slow initial growth and development, with high dry matter production at the end of the cycle and high capacity to produce seeds. The species depends on the light to appear, being that the greater amount of straw, lower are the number of plants and dry weight. The increased soil density elevates the percentage of emergency, but reduces the growth of the plant. The number of leaves is not affected by alteration of soil density. The increment in soil pH decreases the dry weight of the plant, but does not interfere on other features such as percentage of emergency, number of leaves per plant, height, length and volume of roots.